Isolation of phosphate-solubilizing rhizosphere fungi from jabon merah (Neolamarckia macrophylla) stand of Sidrap Provenance, South Sulawesi. Issue 1 (November 2021) - Jufri, S W; Rahim, I; Arif, A; Restu, M; Iswanto, I; Larekeng, S H
Abstract: Phosphate is an essential macro element that has a necessary function as a constituent of ATP and DNA in plants. However, the availability of dissolved phosphate in the soil is minimal because it tends to bind with soil minerals to form phosphate complexes. With rhizosphere fungi, the low available phosphate in the soil can be overcome. This study aimed to determine the character and potential of fungi capable of dissolving phosphate. The source of the isolates used was a collection of rhizosphere fungus isolates under the red jabon stand. Purification was carried out using the point method on PDA media. The phosphate dissolving ability test was done using the standard method using liquid pikovskaya media and then analyzed descriptively and quantitatively. Eighteen rhizosphere fungus isolates were observed, two of which could dissolve phosphate, respectively, obtained from isolates JCS16 with a concentration value of 10.48 ppm, JCS 13 with a concentration value of 10.06 ppm.